Why is green finance important? - Jeffrey Sachs; Woo Wing Thye; Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2019)
In 2017, global investment in renewables and energy efficiency declined by 3% and there is a risk that it will slow further; clearly fossil fuels still dominate energy investment. This could threaten the expansion of green energy needed to provide energy security and meet climate and clean air goals. Several developed and developing economies are still following pro-coal energy policies and the extra CO2 generated by new coal-fired power plants could more than wipe out any reductions in emissions made by other nations. Finance is the engine of development of infrastructure projects, including energy projects. Generally financial institutions show more interest in fossil fuel projects than green projects, mainly because there are still several risks associated with these new technologies and they offer a lower rate of return. If we want to achieve sustainable development goals, we need to open a new file for green projects and scale up the financing of investments that provide environmental benefits, through new financial instruments and new policies, such as green bonds, green banks, carbon market instruments, fiscal policy, green central banking, financial technologies, community-based green funds, etc., which are collectively known as "green finance".
Keywords: O44; Q56; Q59; 330; green finance; renewable energy; CO2 emissions; Paris Agreement; sustainable development goals; SDGs